Development of a transboundary model of livestock disease in Europe. Issue 4 (16th July 2021) - Bradhurst, Richard; Garner, Graeme; Hóvári, Márk; de la Puente, Maria; Mintiens, Koen; Yadav, Shankar; Federici, Tiziano; Kopacka, Ian; Stockreiter, Simon; Kuzmanova, Ivanka; Paunov, Samuil; Cacinovic, Vladimir; et al.
Abstract: Epidemiological models of notifiable livestock disease are typically framed at a national level and targeted for specific diseases. There are inherent difficulties in extending models beyond national borders as details of the livestock population, production systems and marketing systems of neighbouring countries are not always readily available. It can also be a challenge to capture heterogeneities in production systems, control policies, and response resourcing across multiple countries, in a single transboundary model. In this paper, we describe EuFMDiS, a continental‐scale modelling framework for transboundary animal disease, specifically designed to support emergency animal disease planning in Europe. EuFMDiS simulates the spread of livestock disease within and between countries and allows control policies to be enacted and resourced on a per‐country basis. It provides a sophisticated decision support tool that can be used to look at the risk of disease introduction, establishment and spread; control approaches in terms of effectiveness and costs; resource management; and post‐outbreak management issues.